The influence of zinc incorporation on the physicochemical properties of zinc doped calcium phosphate / Mohamad Firdaus Abdul Wahid - Abdul Wahid, Mohamad Firdaus (2016)
Calcium phosphate ceramics have generated growing interest in biomedical applications because of the biocompatibility properties. However, calcium phosphate ceramics are not identical enough compared to the mineral components of human bone and teeth. It is observed that bone consists of various substituted ions. Thus, ionic substitutions have been proposed to mimic the bone chemical composition. Ionic substitution can alter the chemical and physical characteristics of calcium phosphate ceramics. In addition, having hydroxyapatite and P-tricalcium phosphate as biphasic mixture is favourable for biomedical applications such as bone defect repair. In this study, several zinc concentrations (0, 5, 10 and 15 mol%) were substituted and the characteristics such as phase composition, crystallinity (the fraction of completely crystallised phase), crystallite size (single crystal size), lattice parameters and particle size of the as-synthesized samples were evaluated. The result shows with increased zinc content, the XRD peaks were broadening, the lattice parameters were decreased, the crystallite size and crystallinity of the as-synthesized samples were also decreased. Then, based on thermogravimetric analysis, the as-synthesized samples were calcined at several ca lcination temperatures (600, 700, 800, 900, 1000 °C) to identify the suitable biphasic mixture ratio. In calcination process, hydroxyapatite phase in all samples was stable at 600 °C and started to decompose into P-tricalcium phosphate at 700 °C. Calcination temperature at 700°C was chosen as pre-sintering temperature since hydroxyapatite phase was the dominant phase for zinc substituted calcium phosphate ceramics. The effects of sintering temperatures from 900 to 1100 °C on the samples in terms of phase stability, physical and mechanical properties were determined. The sintered samples showed an increase in P-tricalcium phosphate phase in all samples and formation of a-tricalcium phosphate phase in sintering temperature of 1100 °C. An increase in density was observed in all samples as sintering temperature increased. 5 mol% zinc substituted showed the highest density value o f 2.94 g/cm3 at the sintering temperature of 1000 °C while the compressive strength was found to be higher at 112 MPa and the hardness value at 2.0 GPa. The hardness value and compressive strength decreased with further increase in zinc content at the same sintering temperature. This study demonstrated that the properties of calcium phosphate can be tailored by ionic substitution and affected the calcination and sintering behaviour process.